Congestion Charging in London - Richards, Martin G. author. aut Link
XVII, 303 p.
Keywords: Ken Livingstone was elected Mayor of London on a platform that included a congestion charge for central London, a policy that became reality on 17 February 2003. Richards uses his experience as Director of a £2.5 million Government congestion charging study, as one of those who created the scheme Livingstone adopted and as advisor to the London Assembly, to provide a critical record of the introduction of the London Congestion Charge, and of its implications for congestion charging elsewhere.